Persepsi Wisatawan Domestik Terhadap Kualitas Pelayanan Desa Wisata Kete’kesu Toraja Utara - Dai, Nur Fajrin; lagalo, Anggraeni; Sunarti, Sri (Program Studi S1 Pariwisata, Universitas Muhammadiyah Gorontalo, 2022)
Perception is an impression that is obtained by individuals or groups through the five senses and then organized, interpreted and evaluated so as to obtain meaning. Service quality is the ability of a company to provide services that have a direct impact on customer satisfaction in accordance with their wants and needs. A tourist village is a rural area that offers an overall atmosphere that reflects the authenticity of the countryside both from socio-economic life, socio-culture, customs, daily life, has a typical village architecture and spatial structure, or economic activities that are unique and interesting and have the potential to the development of various tourism components, such as attractions, accommodation, food-beverages and other tourism needs. This study aims to determine the Perceptions of Domestic Tourists on Service Quality.This research aims to determine the Perception of Domestic Tourists toward Service Quality. This research used a quantitative descriptive approach. The sample was taken technically with a total sample of 85 respondents. Data collection using observation sheets and questionnaires. Data analysis using the Likert scale on the tourist perception validity test of <0.05=0.05 and Cronbach’s alpha result of 0.708 on service quality and hypothesis test with a value of 0.000 using the multivariate regression method. So, there is an influence on tourist perceptions of the quality of service.